A five-antigen Esx-5a fusion delivered as a prime-boost regimen protects against M.tb challenge - Stylianou, Elena; Pinpathomrat, Nawamin; Sampson, Oliver; Richard, Alexandre; Korompis, Marcellus; McShane, Helen (Frontiers in Immunology, 2023)
The development of tuberculosis (TB) vaccines has been hindered by the complex nature of Mycobacterium tuberculosis (M.tb) and the absence of clearly defined immune markers of protection. While Bacillus Calmette-Guerin (BCG) is currently the only licensed TB vaccine, its effectiveness diminishes in adulthood. In our previous research, we identified that boosting BCG with an intranasally administered chimpanzee adenovirus expressing the PPE15 antigen of M.tb (ChAdOx1.PPE15), improved its protection. To enhance the vaccine's efficacy, we combined PPE15 with the other three members of the Esx-5a secretion system and Ag85A, into a multi-antigen construct (5Ag). Leveraging the mucosal administration safety of ChAdOx1, we targeted the site of M.tb infection to induce localised mucosal responses, while employing modified vaccinia virus (MVA) to boost systemic immune responses. The combination of these antigens resulted in enhanced BCG protection in both the lungs and spleens of vaccinated mice. These findings provide support for advancing ChAdOx1.5Ag and MVA.5Ag to the next stages of vaccine development.